Large-scale cortico-subcortical functional networks in focal epilepsies: The role of the basal ganglia - Výtvarová, Eva; Mareček, Radek; Fousek, Jan; Strýček, Ondřej; Rektor, Ivan (NeuroImage. Clinical, 2017)
OBJECTIVES: The aim was to describe the contribution of basal ganglia (BG) thalamo-cortical circuitry to the whole-brain functional connectivity in focal epilepsies. METHODS: Interictal resting-state fMRI recordings were acquired in 46 persons with focal epilepsies. Of these 46, 22 had temporal lobe epilepsy: 9 left temporal (LTLE), 13 right temporal (RTLE); 15 had frontal lobe epilepsy (FLE); and 9 had parietal/occipital lobe epilepsy (POLE). There were 20 healthy controls. The complete weighted network was analyzed based on correlation matrices of 90 and 194 regions. The network topology was quantified on a global and regional level by measures based on graph theory, and connection-level changes were analyzed by the partial least square method. RESULTS: In all patient groups except RTLE, the shift of the functional network topology away from random was observed (normalized clustering coefficient and characteristic path length were higher in patient groups than in controls). Links contributing to this change were found in the cortico-subcortical connections. Weak connections (low correlations) consistently contributed to this modification of the network. The importance of regions changed: decreases in the subcortical areas and both decreases and increases in the cortical areas were observed in node strength, clustering coefficient and eigenvector centrality in patient groups when compared to controls. Node strength decreases of the basal ganglia, i.e. the putamen, caudate, and pallidum, were displayed in LTLE, FLE, and POLE. The connectivity within the basal ganglia-thalamus circuitry was not disturbed; the disturbance concerned the connectivity between the circuitry and the cortex. SIGNIFICANCE: Focal epilepsies affect large-scale brain networks beyond the epileptogenic zones. Cortico-subcortical functional connectivity disturbance was displayed in LTLE, FLE, and POLE. Significant changes in the resting-state functional connectivity between cortical and subcortical structures suggest an important role of the BG and thalamus in focal epilepsies.
Keywords: dospělí; Epilepsies, Partial; Magnetic Resonance Imaging; Humans; Image Processing, Computer-Assisted; lidé středního věku; Middle Aged; Oxygen; Young Adult; magnetická rezonanční tomografie; nervová síť; elektroencefalografie; mladý dospělý; Cerebral Cortex; Nerve Net; mužské pohlaví; epilepsie parciální; mapování mozku; Adult; Neural Pathways; Basal Ganglia; mozková kůra; počítačové zpracování obrazu; Electroencephalography; kyslík; nervové dráhy; ženské pohlaví; Brain Mapping; lidé; Aged; senioři; Male; bazální ganglia; Female